The Zafindraony Chant: Indigenous Appropriation and Cultural Resilience within Betsileo Protestantism - Rafenomanantsoa Emilson (Britain International for Academic Research (BIAR-Publisher), 2026)
This study explores the Zafindraony as a dynamic cultural archive within the Betsileo socio-religious ecosystem. Emerging during the nineteenth century at the intersection of Merina political expansion and Protestant missionary influence, the Zafindraony has evolved from a liturgical adaptation into a sophisticated repository of indigenous identity. Through archival hermeneutics, comparative ethnomusicological analysis, and ethnographic fieldwork conducted across Fianarantsoa, Ambositra, and Ambalavao, this research examines the genre’s diachronic development and its role in communal cohesion. The findings demonstrate that the Zafindraony operates as a site of strategic syncretism, where Western four-part harmonic structures are re-contextualized to house traditional anatra (moral counsel) and ancestral metaphors. The genre functions as a living instrument of resilience, providing emotional scaffolding during communal rites such as funeral vigils (lanonana) and facilitating social solidarity in an era of rapid digitization. By cross-referencing colonial documentation with contemporary oral testimonies, this study reveals how the Betsileo reclaimed the genre to safeguard their philosophical and linguistic heritage against the risks of cultural homogenization. Ultimately, this article advocates for the formal integration of Zafindraony studies into the Malagasy higher education curriculum. Treating the genre as a vital national heritage asset rather than a peripheral liturgical relic is essential for its preservation. By legitimizing the Zafindraony within the Malagasy academy, this research contributes to the decolonization of musicological discourse, ensuring that this evolving polyphonic tradition continues to serve as an engine for communal development, spiritual well-being, and enduring cultural sovereignty for future generations of the Betsileo people.